PENGARUH TEKNIK CROSS LINE TERHADAP PEMAHAMAN KONSEP PERKALIAN DAN KEAKTIFAN SISWA SD NEGERI LUWUNGRAGI 01 - Auliatul Faizah, Vina; Tri Setiyoko, M.Pd, Didik; Toharudin, M.Pd, Dr. Moh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low understanding of multiplication concepts and student activeness in elementary mathematics learning remains a challenge that affects learning outcomes. This condition is caused by learning practices that tend to emphasize memorization and teacher-centered instruction, resulting in students having difficulty understanding multiplication concepts meaningfully. This study aimed to determine the effect of the cross line technique on students’ understanding of multiplication concepts and learning activeness in Grade III elementary school students. The research employed a quantitative approach with an experimental method using a Posttest-Only Control Group Design. The population consisted of 80 Grade III students of SD Negeri Luwungragi 01, Brebes Regency, in the 2025/2026 academic year. Sampling was conducted using saturated sampling, involving all students as research subjects. Class IIIA was assigned as the experimental group receiving instruction through the cross line technique, while Class IIIB served as the control group receiving conventional multiplication instruction. Data were collected through essay tests and student activeness questionnaires and analyzed using normality tests, homogeneity tests, and independent sample t-tests. The findings revealed that the mean posttest score of multiplication concept understanding in the experimental class was 79.6, higher than the control class score of 72.8. Furthermore, the mean activeness score in the experimental class was 86, while the control class obtained a score of 78. Hypothesis testing indicated a significance value of less than 0.05, demonstrating that the cross line technique significantly affects students’ understanding of multiplication concepts and learning activeness. Therefore, the cross line technique can be used as an effective alternative in elementary mathematics learning.